Medication Errors in Psychiatric Hospitals: A Nationwide Real-World Evidence Study in Saudi Arabia - Khalidah A. Alenzi; Mona Y. Alsheikh; Deemah S. Alsuhaibani; Yasser Alatawi; Thamir M. Alshammari (Pharmaceuticals)
Background: Medication errors are among the most prevalent medical errors and result in significant morbidity and mortality. They pose a major threat to patient safety in psychiatric hospitals. However, the lack of a comprehensive investigation into the root causes of these errors restricts the development of effective corrective measures. Objective: This study aimed to characterize the types of errors, determine the stages of the medication use process, and identify factors associated with errors occurring among government psychiatric hospitals in Saudi Arabia. Methods: This cross-sectional study was conducted from August 2019 to June 2020. All medication error reports submitted to the Ministry of Health General Administration of Pharmaceutical Care database from 18 government psychiatric hospitals in Saudi Arabia were assessed. The database is de-identified and contains information on all medication errors, including patient demographics, medication information, error information, causes of errors, and reporter information. Medication use was categorized as ordering/prescribing, transcribing, dispensing, administration, and monitoring. The present findings represent a descriptive analysis of the data using Statistical Analysis Software (SAS) version 9.4. Result: A total of 23,355 medication error reports were reported to the database during the study period. Among Saudi Arabian cities, Riyadh (n = 8972, 38.4%) had the highest medication error reporting rate, followed by Taif (n = 3705, 15.9%) and Jeddah (n = 2621, 11.2%). Most reported errors were frequently made by physicians (n = 20,284, 86.9%) and were primarily detected by pharmacists (n = 20,974, 89.8%). Approximately half of them (n = 13,150, 56.3%) were classified as “Category B” that occurred, but they did not reach patients. Most medication errors were reported in adults (n = 22,589, 96.7%) and male patients (n = 16,393, 70.2%). Most error reports were detected at the prescription stage (n = 16,481; 70.6%) during the medication-use process. Work overload of the staff (n = 2911, 12.8%) and drug labeling, packaging, and nomenclature (n = 2826, 12.1%) were the most common contributing factors associated with the reported errors. Olanzapine (n = 1650, 7.1%), omeprazole (n = 1350, 5.8%), and quetiapine (n = 1273, 5.5%) were the most common medications associated with medication errors. Conclusions: Preventable medication errors are typical in psychiatric hospitals and may result in severe consequences. Increased efforts are needed to control and minimize prescribing errors and improve reporting in Saudi Arabia.